From nano- to macro-engineering of oxide-encapsulated-nanoparticles for harsh reactions: one-step organization via cross-linking molecules. Issue 80 (16th September 2016) - Zhang, Qiaofei; Zhao, Guofeng; Zhang, Zhiqiang; Han, Lupeng; Fan, Songyu; Chai, Ruijuan; Li, Yakun; Liu, Ye; Huang, Jun; Lu, Yong
Abstract : One-step "macro–micro–nano" organization is reported to embed oxide-encapsulated-nanoparticles onto monolithic-substrates via molecularly-defined cross-linking agents, for applications in exothermic and/or high-throughput reaction processes. Abstract : A strategy of "macro–micro–nano" organization is reported for embedding oxide-encapsulated-nanoparticles onto monolithic substrates in one-step with the aid of molecularly defined cross-linking agents. Such catalysts, with enhanced heat/mass transfer and high permeability, are qualified for several harsh reaction processes such as CH4 /VOC abatement, gas-phase hydrogenation of dimethyl oxalate and oxidative dehydrogenation of ethane.